2021
DOI: 10.25304/rlt.v29.2555
|View full text |Cite
|
Sign up to set email alerts
|

Learning to teach mathematics with robots: Developing the ‘T’ in technological pedagogical content knowledge

Abstract: A multiple case study was conducted to investigate how Lego robotics instruction incorporated into a middle grades mathematics methods course could inform pre-service teachers’ (PSTs) TPACK through the lens of Social Constructivist Theory. The qualitative data analysis revealed that when instruction on Lego robotics technology is integrated into semester long mathematics methods courses, PSTs are able to improve their TPACK knowledge in regard to the robotics. Overall, the findings suggest instruction of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…This is due to the skills of the 21st century science students are encouraged to have high-level thinking skills in solving a problem. The TPACK learning model encourages a teacher to master 21st century technology (Casler-Failing, 2021). Not only that, the TPACK learning model is able to improve student learning outcomes in distance learning (Kaleli, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the skills of the 21st century science students are encouraged to have high-level thinking skills in solving a problem. The TPACK learning model encourages a teacher to master 21st century technology (Casler-Failing, 2021). Not only that, the TPACK learning model is able to improve student learning outcomes in distance learning (Kaleli, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The fourth research question was concerned with distribution AI in term of publication year (Figure 6). In 2021 the percentage number of articles published on AI is the highest compared to other years (30%) (Casler-Failing, 2021;Harper et al, 2021;Mills, 2021;Seckel et al, 2021;Wu, 2021;Zakaria et al, 2021). This was followed by percentage in 2020 (20%) (Gulz et al, 2020;Lopez-Caudana et al, 2020;Saha et al, 2020;Salas-Rueda et al, 2020), while in 2019 has the same number of percentage of articles published as in 2020 (20%) (Forsström & Afdal, 2019;Rico-Bautista et.…”
Section: The Distribution Of Ai In Term Of Publication Yearmentioning
confidence: 95%
“…One form of technology that has been shown to be beneficial to the learning of mathematics is LEGO robotics, namely EV3 Mindstorms. Select children and educators have had access to LEGO robotics for the past 20 years however, robotics has not experienced widespread use in the mathematics classroom, in a middle-school mathematics classroom working with LEGO robotics demonstrated that robotics could provide richer learning and engagement than traditional 'I do, we do, you do' instruction (Casler-Failing, 2021). Therefore, in the current work, we follow the idea of Ouyang and Jiao (2021) as conceptual framework namely AI-directed (learner-as-recipient), AI-supported (learner-as-collaborator), and AI-empowered 9 learner-as-leader).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…In light of the above, and as further explained in the next section, this study aims to create conditions for PST to: experience the integration of ER in practical and contextualized situations (Casler-Failing, 2021;Huang & Zbiek, 2017), contacting with different ER platforms (Anwar et al, 2019;Schina et al, 2021b), aiming at increasing their acceptance of ER with the purpose of facilitating proper integration into their teaching practices (Davis, 1989;Rafique et al, 2020), allowing PST to participate in collaborative tasks that integrate ER with their peers (Anwar et al, 2019;You et al, 2021), create and implement learning scenarios in real classroom setting (Tankiz & Uslu, 2022;You et al, 2021), and reflect on this process (Schina et al, 2021b;Seckel et al, 2022). To adjust the intervention design we collected PST perceptions of ER regarding:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By including different ER platforms in this intervention (Anwar et al, 2019;Schina et al, 2021b), we sought to contribute to the acceptance of this technology by the participants (Casey et al, 2021;Davis, 1989;Schina et al, 2021aSchina et al, , 2021b. Each of the four didactic sequences in this stage was dedicated to distinct mathematical contents in order to enable PST to experience the integration of ER in practical and contextualized situations (Casler-Failing, 2021;Huang & Zbiek, 2017) and promote curricular articulation and integration (El-Hamamsy et al, 2021;Kim, 2019;Sapounidis & Alimisis, 2021) for each of the primary school years of the context in which PST practicum took place. All didactic sequences followed the same format, allowing PST to experience mathematical tasks that integrate ER and facilitate their understanding of the process of adapting and creating learning scenarios to the specific context of the practicum.…”
Section: Pedagogical Interventionmentioning
confidence: 99%